1988
DOI: 10.1523/jneurosci.08-10-03616.1988
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic transmitters and depolarizing influences regulate development of the substantia nigra in culture

Abstract: Recent evidence suggests that extracellular signals regulate neurotransmitter traits in brain catecholaminergic (CA) neurons as in the periphery. Development of the dopaminergic phenotype in the mouse substantia nigra (SN) was studied by monitoring tyrosine hydroxylase (TH), the rate-limiting enzyme in CA biosynthesis in vivo and in culture. Explants of SN were dissected from embryonic day 15 embryos and grown in culture for a week. To define the influence of depolarizing signals on central dopaminergic neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…In the present study, multiple veratridine stimulations increased DA release as compared with non‐stimulated control cultures. The increasing effect of multiple veratridine challenges may be explained by increased TH activity (Friedman et al. , 1988) due to increased phosphorylation of the enzyme (Witkovsky et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, multiple veratridine stimulations increased DA release as compared with non‐stimulated control cultures. The increasing effect of multiple veratridine challenges may be explained by increased TH activity (Friedman et al. , 1988) due to increased phosphorylation of the enzyme (Witkovsky et al.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of primary cultures of mouse olfactory bulb with high KCl (40–50 m m ) for 48 h increases the number of TH + neurons at least twofold and causes alterations in neurite outgrowth (Cigola et al. , 1998), and long‐term treatment with low concentrations of veratridine enhances TH activity and protein expression in organotypic cultures of mouse ventral mesencephalon (Friedman et al. , 1988) and improves survival of dopaminergic neurons in rat primary mesencephalic cultures (Salthun‐Lassalle et al.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the tachykinin agonists might be simply to restore the expression of TH within neurons that contain undetectable amounts of the enzyme as they entered a premorbid state (Hirsch et al, 1988;Michel and Agid, 1996). Even though tachykinins were reported to stimulate TH protein expression (Friedman et al, 1988), this possibility is doubtful, because the tachykinin agonists failed to rescue the fraction of TH ϩ neurons that had already disappeared when initiation of the treatments was delayed. The observation that the pancaspase inhibitor Boc-D-FMK was also able to increase the number of DA neurons in this model system indicates that the tachykinins probably reversed an ongoing apoptotic process that is occurring spontaneously (Salthun-Lassalle et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We examined the SN in culture and found that depolarizing stimuli increased TH activity, and that this rise was attributable to an increase in TH enzyme protein, that is, was true enzyme induction (34). Moreover, in the case of the SN we were able to examine the effects of the physiologic presynaptic transmitters, because these had been identified; the SN appears to receive an excitatory SP-containing pathway from the striatum (35).…”
Section: Molecular Information In Other Brain Systemsmentioning
confidence: 99%